QUALITY OF Tetraselmis sp. CULTURED BY TIGER SHRIMP AQUACULTURE WASTE AS FERTILIZER - Nisa, Andina Chairun (Chanos Chanos, 2023)
Tiger shrimp aquaculture waste still contained amount of nutrients needed by phytoplankton for its growth. Among nutrients was resulted from intensive aquaculture still can be used by phytoplankton. Phytoplankton used nitrates and phosphates for its growth and development. Phytoplankton requires nitrate concentration in 0,9-3,5 mg/ and phosphate in 0,27-5,51 mg/l. Utilization of tiger shrimp aquaculture waste for Tetraselmis sp. quality can be seen using fluorescence microscope with the cell of Tetraselmis sp. had to stained by acridine orange before observed using fluorescence microscope. The concept of this staining when cells of Tetraselmis sp. radiated green colour showed that cells was alive whereas cells radiated orange colour showed that cells was dead or damaged. This matter caused living cells could reducted acridine orange pigment enzymatically until become green radiated cells, instead damaged cells showed orange colour. Research procedures included cultivating Tetraselmis sp. in various dosages waste of tiger shrimp aquaculture as fertilizer. This various dosages are 2 g/l, 4 g/l, 6 g/l and 8 g/l. Culture media for Tetraselmis sp. was saltwater. Sterile saltwater was put into jars about 1 L and later added wastewater to jars. Reading of protein expression helped using imageJ software that showed histogram graphics accompanied by mean. Mean resulted by graphics indicated protein could be expressed. Based on expression of fluorescence protein with 2 g/l wastewater dosage showed that amount of protein could be ecpressed was higher than other wastewater dosage by mean value from ImageJ.